Financial System Standards and Financial Stability : The Case of the Basel Core Principles - Marston, Dewitt (IMF Working Papers; Working Paper ;, 2001)
The relationship between the observance of financial system standards and financial stability is complex owing to the multitude of macroeconomic and structural factors affecting stability. Therefore, assessments of standards in terms of technical criteria for compliance needs to be reinforced with additional information on other factors affecting risks in order to assess financial stability. Preliminary evidence from country data on observance of Basel Core Principles (BCPs) suggests that indicators of credit risk and bank soundness are primarily influenced by macroeconomic and macroprudential factors and that the direct influence of compliance with Basel Core Principles on credit risk and soundness is insignificant. BCP compliance could, however, influence risk and soundness indirectly through its influence on the impact of other macro variables.